Molecular genetics of Dupuytren’s contracture - Aissvarya, Shankar; Ling, King-Hwa; Arumugam, Manohar; Thilakavathy, Karuppiah (British Editorial Society of Bone and Joint Surgery, 2024)
• Dupuytren’s contracture (DC) is a fibroproliferative disorder of the palmar fascia characterised by the digits’ flexion contractures and is associated with abnormal build-up of type III collagen. The prevalence of the disease is reported to be highest among Northern European descendants. However, the disease is widespread globally with varying prevalence. • DC is a multifactorial disease, having both genetic and environmental factors contributing to the causality of the disease. • Over the years, various studies have been conducted to understand the molecular mechanism and genetic aspects of DC but there is a lack of reports on the variants found in the exonic regions. Most reports are backdated making it necessary to re-evaluate the variants to further understand the genetic aetiology of DC. • In this review, we first highlight the genetic aspects and previous genetic studies on DC. The report is followed by a discussion on the molecular pathways suggested to be associated with DC and a summary of the genetic variants in the exonic regions found in DC and their connections with the molecular pathways. • A total of nine variants were reported originating from six genes comprising three pathways. Most variants reported are involved in the Wnt signalling pathway. Moreover, all variants identified are in European/Caucasian subjects and the variants found in the exonic regions are missense variants. • A comparison of these findings with variants from populations of other regions can be conducted to identify the variants with the most occurrence to act as biomarkers or therapeutic targets for DC.